Jawabanmu

2014-09-03T17:16:31+07:00
2.     a. (-3m+4n-6)-(7n-8m+10) = -3m+4n-6-7n+8m+10
                                              = -3m+8m+4n-7n-6+10
                                              = 5m-3n+4
       b. (15a+7b-5c)-(-11a-12b+13d) = 15a+7b-5c+11a+12b-13d
                                                    = 15a+11a+7b+12b-5c-13d
                                                    = 26a+19b-5c-13d
3. (5x - 6y + 8z) + (7x - 9z) - (2y + 9z - 10) = 5x - 6y + 8z + 7x - 9z - 2y + 9z - 10 
                                                               = 5x + 7x - 6y - 2y + 8z - 9z + 9z - 10
                                                               = 12x - 8y + 8z - 10